Etika Pendidikan dalam Perspektif Imam Ghazali - Ulum, Miftachul; Mun'im, Abdul (Journal of Islamic Education, 2024)
According to Imam Ghazali, knowledge is to a person's heart like food and drink are to a person's body. We can imagine that if someone does not eat and does not drink, the same goes for someone's heart without knowledge. We can imagine if humans did not eat or drink. The aim of this research is to describe ethics in learning in the study of the book Minhajul Muta'allimin by Imam Ghazali. Library research method with the main source being the book Minhajul Muta'allimin and other sources either from journals or other sources. The research results show that the success and benefits of the knowledge gained by students is when a student is able to understand his duties and obligations in studying.   A student must intend to seek knowledge and always hope for the blessing of Allah SWT.